Clinical pilot study to evaluate the neovaginal PACIENA prosthesis® for vaginoplasty without skin grafts in women with vaginal agenesis - Pedro Acién; Francisco J. Nohales-Alfonso; Maria-Luisa S; Miguel Sánchez-Lozano; Victoria Navarro-Lillo; Maribel Acién (BMC, 2019)
Abstract Background To evaluate the feasibility and clinical outcomes of vaginoplasties using a neovaginal polylactic acid prosthesis made with 3-dimensional (3D) printing technology as an intraneovaginal mould. Methods This was an interventionist, prospective, and multicentre clinical pilot investigation of a sanitary product (PACIENA prosthesis®) aiming to recruit and operate on 8 patients over 6 months with a follow-up period of 6 months. Only six patients with Rokitansky syndrome and one patient with Morris syndrome (7 patients in total) were operated on in two university hospitals: "La Fe", Valencia (H1) and "Arrixaca", Murcia (H2). Interventions: Extensive surgical dissection of a defined space between the urethra and bladder in the front and of the rectum in the back as well as insertion of the PACIENA prosthesis® covered with Interceed® were performed. After 12 days, the prosthesis was changed to the silicone-covered version for daily application. Results In the 6 patients with Rokitansky syndrome (86%), the primary endpoint (satisfactory vaginal outcome in terms of appearance, function, and sensation without relevant additional morbidity) was achieved, although only 2 patients (28%) were sexually active at the end of 6 months of follow-up. The patient with Morris syndrome withdrew from the study after 1 month. Patients without bacterial colonization showed positive Schiller tests at 1 month, and subsequent biopsies showed adequate keratinization and epidermization. Epithelization and iodopositivity were delayed in the patients who developed inflammatory granulomas. Conclusions Good anatomical and functional results can be achieved with the PACIENA prosthesis® for vaginoplasties without skin grafts. However, adequate patient selection and education, good surgical techniques and haemostasis, postoperative support, and prevention of bacterial colonization are important. Trial registration This clinical study was approved by the Ethical Clinical Investigation Committee of San Juan University Hospital on September 27, 2016, to be conducted in the participating centres; it was authorized by the Spanish Agency of Medicines and Health Products (AEMPS) on April 24, 2017 (exp. no. 585/16/EC), to be carried out in that hospitals.